PENGARUH PENGENDALIAN PERSEDIAN BAHAN BAKU TERHADAP PROSES PRODUKSI PRODUK USAHA KERIPIK WAHYU KOTA LUWUK - Nurnajamuddin, Mahfud; Suriyanti, Suriyanti; Saudin, La (Yayasan Education and Social Center, 2024)
The purpose of this study is to determine whether the Influence of Raw Material Inventory Control has a positive and significant effect on the Production Process of Wahyu Chips Business Products in Luwuk City. The research sample was employees at Wahyu Chips Business in Luwuk City. using purpose sampling technique with a total of 30 people. Data collection methods used interviews and questionnaires. Data were analyzed descriptively quantitatively using frequency tables and simple linear regression. The results of data processing were carried out through the SPSS version 25.0 program. From the results of the t-test, it was found that the independent variable, namely Raw Material Inventory Control (X), had an influence on the Production Process of Wahyu Chips Business Products (Y) in Luwuk City. The results of the study showed that Raw Material Inventory Control (X) had a dominant and significant influence with a coefficient value of 1.080, which means that Raw Material Inventory Control has an influence on the Production Process of Wahyu Chips Business Products in Luwuk City